O jezikovnih napakah pri pisnem izražanju gluhih srednješolcev - Kuplenik, Nicole (Jezik in slovstvo, 1999)
The article presents an empirical analysis of the surface language structure of deaf secondary-school students of the Institut for Deaf and Hard-of-Hearing of Ljubljana, as manifested in their written texts. Reasons for the poor linguistic structure of their writing, which are a matter of deep (psycholingvistic) analysis, are not discussed here. Only the witten language of deaf secondary-school students of the Institut is analysed, while the language of deaf students of regular secundary schools, who have succesfully overcome the language barrier, is not included.
Keywords: Slovene; slovenščina; napake; gluhi; srednje šole